MAQÂSHID SYARÎ’AH DALAM FATWA DEWAN HISBAH PERSIS - Huda, Alamul (Fakultas Syariah, 2014)
This article discuss about Hisbah Council (Dewan Hisbah) as an institution of The Organisation of Islamic Unity (PERSIS) which has the authority to product fatwa. This research is aimed to elaborate the concept of maqâshid syarî’ah used by Hisbah Council in issuing fatwa. To issue fatwa, they use the methodology (manhaj) and system (thurûq) that has the character and ideology to implements the concept of back to the al Qur’an and al Sunnah. It means that the fuqaha who engaged in Hisbah Council makes and put of school (madhab) position